2020
DOI: 10.1038/s41598-020-70291-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of umbilical cord stem cells labeled with superparamagnetic iron oxide nanoparticles: effects of labelling and transplantation parameters

Abstract: cell tracking with magnetic resonance imaging (MRi) is important for evaluating the biodistribution of transplanted cells. Umbilical cord-derived mesenchymal stem cells (UC-MSCs) have emerged as a promising therapeutic tool in regenerative medicine. We examined the Uc-MScs labeled with superparamagnetic (Spio) and ultrasmall superparamagnetic iron oxide (USpio) in terms of cell functioning and imaging efficiency in vitro and in vivo. The UC-MSCs were co-incubated with SPIO or USPIO at a concentration of 50 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
(50 reference statements)
3
17
0
Order By: Relevance
“…The ability of MSCs to migrate from one hemisphere to another has also been demonstrated in other studies [87]. In other reports [88][89][90][91][92][93], MSCs injected intracerebrally were detectable at the site of administration 1-3 weeks after injection, with a subsequent rapid decrease and no significant systemic distribution. Other studies [94] showed that MSCs can be detected with fluorescence and bioluminescence up to 7 weeks after transplantation; (c) Intraventricular injection of MSCs: Some studies showed that MSCs injected into cerebral ventricles are able to migrate to large blood vessels in a brain traumatic injury model [95], and also to brain parenchyma and the spinal cord [96].…”
Section: Injection Of Mscs Into the Central Nervous Systemsupporting
confidence: 67%
“…The ability of MSCs to migrate from one hemisphere to another has also been demonstrated in other studies [87]. In other reports [88][89][90][91][92][93], MSCs injected intracerebrally were detectable at the site of administration 1-3 weeks after injection, with a subsequent rapid decrease and no significant systemic distribution. Other studies [94] showed that MSCs can be detected with fluorescence and bioluminescence up to 7 weeks after transplantation; (c) Intraventricular injection of MSCs: Some studies showed that MSCs injected into cerebral ventricles are able to migrate to large blood vessels in a brain traumatic injury model [95], and also to brain parenchyma and the spinal cord [96].…”
Section: Injection Of Mscs Into the Central Nervous Systemsupporting
confidence: 67%
“…Magnetic resonance imaging (MRI) can be used to track MSCs in vivo by labeling MSCs with superparamagnetic iron oxide nanoparticles (SPIONs) or fluorine-19 ( 19 F). Direct labeling of MSCs with SPIONs is possible as these agents are readily taken up by MSCs and show up as hypointense signals on MRI [ 247 ]. However, some studies have shown that proliferative and differentiation capabilities of MSCs could be affected when labeled at higher concentrations [ 247 ].…”
Section: Introductionmentioning
confidence: 99%
“…Direct labeling of MSCs with SPIONs is possible as these agents are readily taken up by MSCs and show up as hypointense signals on MRI [ 247 ]. However, some studies have shown that proliferative and differentiation capabilities of MSCs could be affected when labeled at higher concentrations [ 247 ]. The downside of SPION labeling is that the specificity of SPION-labeled cells could be low and the signals could be hard to differentiate from acutely injured tissues containing hemorrhages.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, there has been a great development of iron oxide-based magnetic nanoparticles application in many scientific fields, including biomedical engineering [ 1 , 2 ], cell labeling [ 3 , 4 ], cancer treatment [ 5 , 6 , 7 ], magnetic drug delivery [ 8 , 9 ], multimodal imaging [ 10 , 11 ], and Magnetic Resonance Imaging (MRI) contrast agents [ 12 , 13 , 14 ], due to their unique and diverse biomedical properties. Depending on their composition and surface modification, they recently focused attention on the targeted anticancer treatment and mild magnetic hyperthermia (MH) [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%